2022
DOI: 10.1101/2022.03.07.22271986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional, circuit, and network heterogeneity of brain abnormalities in psychiatric disorders

Abstract: The substantial individual heterogeneity that characterizes mental illness is often ignored by classical case-control designs that rely on group mean comparisons. Here, we present a comprehensive, multiscale characterization of individual heterogeneity of brain changes in 1294 cases diagnosed with one of six conditions and 1465 matched healthy controls. Normative models identified that person-specific deviations from population expectations for regional grey matter volume were highly heterogeneous, affecting t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 132 publications
3
33
0
Order By: Relevance
“…Future studies should examine how altered connectivity in patients impacts our findings. Moreover, our findings are dependent on group-level summary metrics of brain volume and may not be representative of volume changes at the individual patient level, which show substantial heterogeneity [67][68][69] . Subsequent work could look at whether using individual-level measures of brain volume and connectivity can improve model predictions.…”
Section: Limitations and Conclusionmentioning
confidence: 87%
“…Future studies should examine how altered connectivity in patients impacts our findings. Moreover, our findings are dependent on group-level summary metrics of brain volume and may not be representative of volume changes at the individual patient level, which show substantial heterogeneity [67][68][69] . Subsequent work could look at whether using individual-level measures of brain volume and connectivity can improve model predictions.…”
Section: Limitations and Conclusionmentioning
confidence: 87%
“…Additionally, focusing on a particular diagnostic category assumes homogeneity of symptoms and mechanisms (i.e., the homogeneity assumption) 94 , but it is well known that people with the same diagnosis may exhibit little to no overlap in symptoms (i.e., the heterogeneity problem) 95 . Recent neuroimaging studies have attempted to characterize such within-diagnosis heterogeneity at a neural level [219][220][221][222][223][224] . Co-morbidity between putatively distinct disorders (i.e., the comorbidity problem) 76 , and issues of arbitrary clinical cut-offs and subthreshold symptomatology 44,45 are well-documented limitations of current psychiatric taxonomies 225,226 .…”
Section: Box 2 -Limitations Of Traditional Approaches To Psychiatric ...mentioning
confidence: 99%
“…While ASD is primarily characterized by impairments in social communication skills and by repetitive behaviors, a SZ diagnosis consists of positive (e.g., hallucinations, delusions) and negative (e.g., social withdrawal) symptoms. The heterogeneity of both diagnostic categories (Benkarim et al, 2022; Segal et al, 2022) and their phenotypic overlap (Kästner et al, 2015) can hinder accurate diagnosis. More precisely, ASD and SZ co-occur in approximately 4% of cases (Lai et al, 2019), and share both social (Oliver et al, 2020) and sensory-motor deficits (Du et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a recent meta-analysis also showed that comorbidity of ASD and SZ has a 4% prevalence (Lai et al, 2019). However, given the substantial heterogeneity in both SZ and ASD (e.g., Segal et al, 2022), it is difficult to ascertain to which extent and in which brain areas or networks there is overlap between the two diagnoses.…”
Section: Introductionmentioning
confidence: 99%